Discovery of single nucleotide polymorphism in Gossypium hirsutum and G. barbadense through next generation sequencing approach - Sudakara, Reddy S.; Katageri, I. S.; Kumar, N. V. Mohan; Jadhav, M. P.; Adiger, Sateesh; Chakravartty, Navajeet; Vamadevaiah, H. M.; Reddy, V. B. (The Indian Journal of Genetics and Plant Breeding, 2017)
Single nucleotide polymorphism was identified usingddRAD and pooled amplicon sequencing between theallotetraploid cotton genotypes of G. hirsutum var. DS-28(POOL-H) and G. barbadense var. SBYF-425 (POOL-B). The471270 (470161 SNP and 1109 INDELs), 2723 (2621 SNP and102 INDELs) and 780 (759 SNP and 21 INDELs) variant callingwere predicted at read depth of 10 in the genotypes byusing G. raimondii (D5), G. arboreum (A2) and G. hirsutum(AD) as reference genomes, respectively. Further, filteredout false positive homoeologous SNPs between parents(DS-28 and SBYF-425) at read depth of 10, identified 245and 45 homozygous polymorphic SNPs between parentsbased on pooled amplicon sequencing and ddRADsequencing by using G. raimondii, G. arboreum and G.hirsutum as a reference genomes. Based on gene function,5 SNPs were converted into KASPar markers and genotypedin 21 RILs for fibre quality traits. Identified polymorphicSNPs and INDELs can be used for genotyping and QTLmapping after converting into functional markers.